Implementasi Pendidikan Inklusi Di SDN K1 Kabupaten Karawang - Jayadi Jayadi; Asep Supena (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2023)
The concept of inclusive education appears intended to provide a solution to discriminatory treatment in education services, especially for children with disabilities or children with special needs. Not many schools understand how to implement it by involving several communities in order to achieve adequate inclusive education. The purpose of this research is to provide a description of the implementation and problems in inclusive education programs. This research is a qualitative descriptive study using data collection in the form of interviews, observation and documentation. The results of this study are that the implementation model for the implementation of the inclusive education program is going well by making learning tools, implementing inclusion and also evaluating it. While the problem that arises is the lack of understanding from the community and parents about inclusive education so that its implementation needs to be optimized. Human resources owned by schools are still lacking so that they are not optimal in carrying out inclusive education activities and providing services to children with special needs.